Follow me - Searle, Rick.; Searle, Bronwyn (Sydney : Scholastic, 2001)
A story of continuity, of renewal, of the patterns of life that follow on from season to season, generation to generation.
For children.
Keywords: Families -- Juvenile fiction; Cyclones -- Juvenile fiction